Possibility and Effects of Recycling Vinyl-Banner Waste into Fired-Clay Bricks for Home Industry in Lampung - Ikhwanuddin, R.; Maryana, O. F. T.; Darmawan, M. Y.; Anggini, S.; Lailani, A.; Ipmawan, V. L. (Journal of Science and Applicative Technology; Vol 2 No 1 (2019): ICoSITeR Special EditionDO - 10.35472/281429, 2019)
Bricks are regarded as important material in building constructions. Basically, brick is processed by mixing clay and water then burnt under high temperature for a certain duration. Previous study in Indonesia shows that mixing local clay with additional materials could improve its characteristic, especially in terms of water absorption potentiality. Lampung has home industries which run brick making business traditionally. Moreover, this year Indonesian government has been organizing regional elections which attract campaigners to produce more vinyl banners as advertising media. As the event has already passed, vinyl banners eventually become environmental issue since they are not yet well managed. The aim of this study is to investigate the possibility and effect of red bricks mixtures along with vinyl banner waste. Fired-clay bricks dimensions including length, width, and height are 19 cm, 9.5 cm, and 5 cm respectively. Measurement has done by employing water absorption tests. Waste-added bricks absorb more water than the conventional one, about 11% higher. However, rice-husk-ash-added bricks perform similar to the normal bricks, it has slow rate of water absorption. Absorption rate of waste-added bricks also fast and exceed the conventional and RHA-added bricks. Modified red bricks surfaces are uneven, they show cracks and rough edges.